Current state of evaluation of the Ukrainian banking system capitalization - Varenyk, Viktor Anatolijovych (Technology audit and production reserves, 2013)
The article analyzes the level of capitalization of banks in Ukraine in terms of groups, and the prospects for its improvement. The basic rules of small and medium-sized banks development in the context of solving problems of increasing the capitalization of the Ukrainian banking system are considered. Ukrainian banking system capital in terms of bank groups on January 1, 2012 is analyzed. The first bank group demonstrated the excess equity over the statutory onewhile the second, third and fourth bank groups demonstrated the statutory capital excess on their own. Profit as an important source of small and medium-sized capital growth is characterized. The man directions of the Ukrainian banking system capitalization are proposed.